Characterization of L-cysteine sources using ATR-FTIR and Raman spectroscopy - Z., Mohamad Zharif; Tukiran, Nur Azira; Abdullah Sani, Muhamad Shirwan (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2021)
L-cysteine is a food additive that is used in bakery ingredient. It is used as stabilizer to soften the texture of bakery dough. However, the primary sources of L-cysteine could be controversial as it might derive from animal and human parts. This study aimed to differentiate the L-cysteine sources by using Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) and Raman spectroscopy. Raw materials of pig bristles, human hair, cow horn, duck feather and chicken feather were analysed. The result found that the ATR-FTIR is preferable rather than Raman spectroscopy in differentiating the primary sources of L-cysteine. Data pre-treatment was carried out to provide a more suitable for analysis and easier interpretation. Accordingly, principal component analysis (PCA) transformed the transmittance of ATR-FTIR into a number of principal components (PCs).Five distinct groups were successfully differentiated in PCA. The proposed method offers as fast and environmentally friendly approach to distinguish the primary source of L-cysteine sources. Hence, this method would beneficial to be used for origin determination of L-cysteine food additives.